2016
DOI: 10.1186/s12967-016-0775-2
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of miR-483-3p contributes to endothelial progenitor cells dysfunction in deep vein thrombosis patients via SRF

Abstract: BackgroundEndothelial progenitor cells (EPCs) contribute to recanalization of deep vein thrombosis (DVT). This study aimed to detect miRNA expression profiles in EPCs from patients with DVT and characterize the role of miRNA in EPCs dysfunction.MethodsEPCs was isolated from DVT patients and control subjects, and miRNA expression profiles were compared to screen differential miRNAs. The candidate miRNAs were confirmed by RT-PCR analysis. The targets of miRNA were identified by bioinformatics analyses, luciferas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 40 publications
2
66
1
Order By: Relevance
“…MiR-483-5p is down-regulated under hypoxia condition and can inhibit the growth of HUVECs by targeting serum response factor (SRF), which recedes wound healing and tube formation. 110 111 These studies indicate that inhibition of miR-483 enhances angiogenesis of HUVECs. Thus, miR-483 may act as a novel therapeutic target for ischaemic diseases.…”
Section: Mir-483mentioning
confidence: 88%
“…MiR-483-5p is down-regulated under hypoxia condition and can inhibit the growth of HUVECs by targeting serum response factor (SRF), which recedes wound healing and tube formation. 110 111 These studies indicate that inhibition of miR-483 enhances angiogenesis of HUVECs. Thus, miR-483 may act as a novel therapeutic target for ischaemic diseases.…”
Section: Mir-483mentioning
confidence: 88%
“…In recent years, multiple miRNAs have been reported to play a vital role in angiogenesis, cell growth and migration . Our previous studies have demonstrated that miRNAs have a vital role in EPC function . Additionally, miR‐205 has been shown to have different effects on angiogenesis and migration in different types of tumours .…”
Section: Discussionmentioning
confidence: 99%
“…26 Our previous studies have demonstrated that miRNAs have a vital role in EPC function. 11,[27][28][29][30] Additionally, miR-205 has been shown to have different effects on angiogenesis and migration in different types of tumours. [32][33][34][35]42 Meanwhile, miR-205 promotes wound healing in human corneal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations